Strengthening Fiscal Transfers in Indonesia Using an Output-Based Approach - Ellis, Peter; Mandri-Perrott, Cledan; Tineo, Luis (World Bank, Washington, DC, 2012)
In 2010 the World Bank approved a US$220 million loan for a Local Government and Decentralization project in Indonesia. The project aims to improve the accountability and reporting of the central government's Specific Purpose Grants (DAK). Piloted in four infrastructure sub-sectors-irrigation, roads, sanitation, and water the project is the World Bank's first to apply innovative Output-Based Aid (OBA) design principles on a large scale to target improvements in inter-governmental fiscal transfers. Under the project, the DAK grants will work in a similar way to OBA subsidies, which reimburse service providers for independently verified, pre-agreed physical outputs. Up to 81 local governments in five provinces are eligible to take part in this project. This note presents an overview of the project objectives and design.